Lanthanum isomorphous replacement magnetite material, preparation method and application thereof, phosphorus removal agent

Through the preparation method of lanthanum-like replacement magnetite materials, lanthanum ions enter the magnetite lattice, solving the problem of low phosphorus recovery performance of existing lanthanum-based materials, achieving efficient phosphate adsorption and low lanthanum loss. Avoid secondary pollution.

CN116116369BActive Publication Date: 2024-12-20MACAU UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310162986.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-24
Publication Date
2024-12-20
Estimated Expiration
2043-02-24

AI Technical Summary

Technical Problem

The existing lanthanum-based adsorbent materials have low phosphorus recovery performance, resulting in low lanthanum utilization and loss causing secondary pollution.

Method used

The preparation method of lanthanum-like replacement magnetite materials is adopted. By conducting hydrothermal chemical reactions between lanthanum salt and ferrous salt in a weak acid solution, lanthanum ions replace ferrous ions and enter the magnetite lattice to form lanthanum The same-quality replacement magnetite material is used to adsorb phosphate.

Benefits of technology

The phosphorus adsorption efficiency and reusability of lanthanum-based materials are improved, and the lanthanum loss rate is less than 10%, which avoids secondary pollution caused by lanthanum ions entering the water body and maintains an efficient phosphorus adsorption capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116116369B_ABST
    Figure CN116116369B_ABST
Patent Text Reader

Abstract

The present invention provides a lanthanum isomorphous replacement magnetite material, a preparation method and application thereof, and a dephosphorus adsorbent. The preparation method comprises: adding a lanthanum salt and a ferrous salt to a weakly acidic solution, referred to as solution A; adding an alkaline solution to solution A, referred to as solution B; and subjecting solution B to a hydrothermal chemical reaction to obtain a lanthanum isomorphous replacement magnetite material. The present invention selects ferrous salts rather than ferric salts as the replaced material, and simultaneously adds a reducing agent such as ascorbic acid to solution A to prevent the oxidation of divalent iron to trivalent iron, thereby ensuring the replacement of ferrous ions in the magnetite lattice by lanthanum ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmental pollution treatment, in particular to a lanthanum isomorphous substitution magnetite material, a preparation method and application thereof, and a phosphorus removal adsorbent. Background Art

[0002] Lanthanum-based materials are commonly used adsorbents for repairing eutrophic water bodies. The principle is that phosphate in water combines with lanthanum to form lanthanum phosphate, which is insoluble in water, and quickly removes phosphate from the water. At present, most lanthanum-based adsorbent materials load lanthanum on various mesoporous materials, such as zeolite, biochar, halloysite, etc. This method can reduce the agglomeration of lanthanum nanoparticles and enhance the contact between lanthanum and phosphate. The composite material can adsorb more than 100 mg·P / g of phosphate. However, this type of adsorbent has low phosphorus recovery performance, which leads to the problem of low utilization rate of adsorbent lanthanum and secondary pollution caused by loss in practical applications. Summary of the invention

[0003] 1. Technical issues to be resolved

[0004] In view of this, the present invention particularly provides a lanthanum isomorphous substitution magnetite material, a preparation method and application thereof, and a phosphorus removal adsorbent, in the hope of at least partially solving one of the above-mentioned technical problems.

[0005] (II) Technical solution

[0006] According to the first aspect of the present invention, a method for preparing a lanthanum isomorphous substitution magnetite material is provided. The preparation method comprises: adding a lanthanum salt and a ferrous salt to a weakly acidic solution, referred to as solution A; adding an alkaline solution to solution A, referred to as solution B; and subjecting solution B to a hydrothermal chemical reaction to obtain a lanthanum isomorphous substitution magnetite material.

[0007] In some embodiments of the present invention, in the step of adding a lanthanum salt and a ferrous salt to a weakly acidic solution, the lanthanum salt is lanthanum nitrate; the ferrous salt is ferrous sulfate; the weakly acidic solution is an ethylene glycol solution containing a reducing agent; the reducing agent is one or more of the following materials: ascorbic acid, hydrazine hydrate, formic acid, sodium borohydride; and the alkaline solution is an alkaline solution containing hydroxide ions.

[0008] In some embodiments of the present invention, the lanthanum nitrate is lanthanum nitrate hexahydrate; the ferrous sulfate is ferrous sulfate heptahydrate; and the reducing agent is ascorbic acid.

[0009] In some embodiments of the present invention, the molar ratio of lanthanum nitrate hexahydrate to ferrous sulfate heptahydrate is between 1:99 and 1:19.

[0010] In some embodiments of the present invention, the mass concentration of ascorbic acid in the ethylene glycol solution containing a reducing agent is 0.25-1.5 mg / mL.

[0011] In some embodiments of the present invention, in solution A, the total molar concentration of lanthanum ions and ferrous ions is between 6 and 12 mmol / L.

[0012] In some embodiments of the present invention, in the step of adding an alkaline solution to solution A, the alkaline solution is: a sodium hydroxide solution or a potassium hydroxide solution.

[0013] In some embodiments of the present invention, the step of performing a hydrothermal chemical reaction on solution B includes: adding solution B into a hydrothermal kettle and performing a hydrothermal chemical reaction in an oven, wherein the heating temperature of the oven is 200-300° C. and maintained for 6-10 hours.

[0014] In some embodiments of the present invention, before the step of adding the alkaline material to solution A, solution A is maintained at 25-35° C. and stirred by a rotor for 30-60 min.

[0015] In some embodiments of the present invention, after the step of adding the alkaline material to solution A, solution B is stirred for 30 to 60 minutes.

[0016] In some embodiments of the present invention, in the step of adding an alkaline solution to solution A, the alkaline solution is a sodium hydroxide solution with a concentration of 50 to 120 g / L.

[0017] In some embodiments of the present invention, in the step of subjecting solution B to a hydrothermal chemical reaction, the hydrothermal chemical reaction is carried out in a hydrothermal kettle, which is a stainless steel reactor lined with polytetrafluoroethylene.

[0018] According to a second aspect of the present invention, a lanthanum isomorphous substitution magnetite material is provided. The lanthanum isomorphous substitution magnetite material is obtained by the above preparation method, wherein lanthanum ions replace ferrous ions and enter the magnetite lattice.

[0019] According to a third aspect of the present invention, there is provided a use of the above lanthanum isomorphous substituted magnetite material for adsorbing phosphate ions in water purification.

[0020] According to a fourth aspect of the present invention, a dephosphorization adsorbent is provided, which comprises: the above-mentioned lanthanum isomorphous substituted magnetite material.

[0021] (III) Beneficial effects

[0022] It can be seen from the above technical solution that the present invention has at least one of the following beneficial effects compared with the prior art:

[0023] (1) The present invention uses lanthanum-doped magnetite prepared by isomorphous substitution, so that the size of magnetite, which is originally a nano-scale material, is further reduced, and lanthanum is distributed in the magnetite bulk phase, and the specific surface area is relatively increased. Furthermore, the phenomenon of isomorphous substitution in magnetite is utilized to allow lanthanum to replace iron and enter the magnetite lattice. On the one hand, the strong magnetism of magnetite is preserved, which is conducive to the recovery of materials; on the other hand, the loss of lanthanum during regeneration is low.

[0024] (2) Ferrous salts are selected as the replaced material instead of ferric salts, and a reducing agent such as ascorbic acid is added to solution A to prevent the oxidation of divalent iron to trivalent iron, thereby ensuring the replacement of ferrous ions in the magnetite lattice by lanthanum ions.

[0025] Experiments have shown that when iron salts are used as the replaced material, the same reaction conditions cannot cause lanthanum ions to replace iron ions in iron salts due to the larger ionic radius of trivalent iron ions.

[0026] (3) Since the atomic radius of lanthanum is relatively large and is at the limit of its ability to replace divalent iron, the existing isomorphous substitution magnetite preparation technology cannot allow lanthanum to enter the magnetite lattice.

[0027] The present invention adopts a hydrothermal kettle to carry out a hydrothermal chemical reaction, increases the reaction temperature to 200-300°C, and can prepare lanthanum isomorphous substitution magnetite without impurities. Experiments have shown that the conventional technology adopts a coprecipitation reaction in a 90°C water bath pot, which can only prepare a lanthanum hydroxide-magnetite complex.

[0028] (4) In the present invention, lanthanum salt and ferrous salt undergo a hydrothermal chemical reaction in an alkaline solution, and lanthanum ions replace ferrous ions and enter the magnetite lattice to form a lanthanum isomorphous substitution magnetite material, and no other lanthanum phases such as lanthanum hydroxide exist in the product. The lanthanum-based material can still maintain a high phosphorus adsorption efficiency after multiple cycles.

[0029] Experiments have confirmed that the lanthanum isomorphous replacement magnetite material of the present invention has a high adsorption capacity for phosphate pollutants, and its saturated adsorption capacity for phosphate at room temperature is as high as 100-130 mg·P / g. In addition, after 8 desorption-adsorption cycles, the lanthanum loss rate is less than 10%, and the adsorption capacity is maintained at more than 75%. Therefore, the lanthanum isomorphous replacement magnetite material of the present invention can be used to adsorb phosphate ions, and is an adsorbent with good reusability.

[0030] (5) In the present invention, lanthanum ions enter the magnetite lattice and are preserved in the material during the regeneration cycle, so that the newly prepared material maintains a high phosphorus adsorption efficiency after multiple cycles, while avoiding secondary pollution that may be caused by lanthanum ions entering the water body. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1The present invention is a flow chart of the method for preparing the lanthanum isomorphous substitution magnetite material.

[0032] Figure 2 It is a correspondence diagram between the X-ray diffraction spectrum of the lanthanum isomorphous substituted magnetite material prepared in Example 1 and the standard diffraction peak of magnetite.

[0033] Figure 3 This is a transmission electron microscope image of the lanthanum isomorphous substituted magnetite material prepared in Example 1.

[0034] Figure 4 This is the phosphorus absorption curve of the lanthanum isomorphous substituted magnetite material prepared in Example 1 under different phosphate concentration conditions.

[0035] Figure 5 The figure is a comparison chart of the lanthanum loss rate of the lanthanum isomorphous substitution magnetite material and the lanthanum hydroxide-magnetite composite prepared by the method of Example 3 in 8 adsorption-desorption cycles.

[0036] Figure 6 This is a graph showing the change in phosphorus adsorption during each adsorption-desorption cycle of the lanthanum isomorphous substituted magnetite material prepared by the method of Example 3. DETAILED DESCRIPTION

[0037] The purpose of the present invention is to provide a lanthanum isomorphous substitution magnetite material in which lanthanum ions replace ferrous ions and enter the magnetite lattice, in order to improve the phosphorus adsorption efficiency of lanthanum-based materials in water purification applications.

[0038] The present invention firstly provides a method for preparing a lanthanum isomorphous substitution magnetite material. Figure 1 This is a flow chart of the preparation method of the lanthanum isomorphous substitution magnetite material of the present invention. Please refer to Figure 1 The preparation method of the lanthanum isomorphous substitution magnetite material of the present invention comprises:

[0039] Step S1, adding lanthanum salt and ferrous salt into a weakly acidic solution, referred to as solution A;

[0040] Step S2, adding an alkaline solution to solution A, referred to as solution B;

[0041] Step S3, performing a hydrothermal chemical reaction on solution B to obtain a lanthanum isomorphous substitution magnetite material.

[0042] In a preferred embodiment of the present invention, in step S1, the lanthanum salt is lanthanum nitrate; the ferrous salt is ferrous sulfate. Wherein, the lanthanum nitrate is lanthanum nitrate hexahydrate; the ferrous sulfate is ferrous sulfate heptahydrate, and the molar ratio of lanthanum nitrate hexahydrate to ferrous sulfate heptahydrate is between 1:99 and 1:19. Moreover, in solution A, the total molar concentration of lanthanum ions and ferrous ions is between 6 and 12 mmol / L. In addition, the weakly acidic solution is an ethylene glycol solution containing ascorbic acid (its pH value cannot be calculated because it is an organic solution), wherein the mass concentration of ascorbic acid is 0.25 to 1.5 mg / mL. More preferably, before the step of adding the alkaline material to solution A, solution A is maintained at 25 to 35°C and vigorously stirred by a rotor for 30 to 60 minutes to promote the lanthanum salt and the ferrous salt to be fully mixed and reacted in the weakly acidic solution.

[0043] It should be noted that the present invention selects ferrous salts instead of ferric salts as the replaced material, and ascorbic acid is added to solution A to prevent the oxidation of divalent iron to trivalent iron, thereby ensuring the replacement of ferrous ions in the magnetite lattice by lanthanum ions. Experiments have shown that when ferric salts are used as the replaced material, due to the larger ionic radius of trivalent iron ions, the same reaction conditions cannot allow lanthanum ions to replace iron ions in ferric salts.

[0044] Those skilled in the art will appreciate that ascorbic acid is used as a reducing agent during the preparation process to prevent ferrous iron from being oxidized to ferric iron. The ascorbic acid can also be replaced by a reducing agent such as hydrazine hydrate, formic acid, sodium borohydride, etc.

[0045] Among them, the prior art CN107694542A provides a process of using industrial magnetite particles as a precursor, coating them with ferrous iron ore, and then calcining them in a muffle furnace to load lanthanum hydroxide. The prepared product is a composite of magnetite and lanthanum hydroxide, and lanthanum ions cannot be replaced into the crystal lattice of magnetite.

[0046] In a preferred embodiment of the present invention, in step S2, the alkaline solution is: sodium hydroxide solution or potassium hydroxide solution. Specifically, the alkaline solution is sodium hydroxide solution, and its concentration is 50-120 g / L. More preferably, after the step of adding the alkaline material to solution A, solution B is stirred for 30-60 min.

[0047] In a preferred embodiment of the present invention, step S3 comprises: adding solution B into a hydrothermal kettle and performing a hydrothermal chemical reaction in an oven, wherein the oven is heated at a temperature of 200 to 300° C. and maintained for 6 to 10 hours. The hydrothermal kettle is a stainless steel reactor lined with polytetrafluoroethylene.

[0048] It should be noted that the current method for preparing isomorphous replacement magnetite material is to prepare it by low-temperature (<100°C) coprecipitation reaction in a water bath. Since the atomic radius of lanthanum is relatively large, the existing isomorphous replacement magnetite preparation technology cannot make lanthanum enter the magnetite lattice, and only lanthanum hydroxide-magnetite complex can be obtained. The present invention uses a hydrothermal kettle for hydrothermal reaction, increases the preparation temperature to 200-300°C, and controls the ratio of lanthanum to iron, so as to prepare lanthanum isomorphous replacement magnetite without impurities.

[0049] Those skilled in the art should understand that the present invention adopts a method for preparing lanthanum-doped magnetite by isomorphous replacement, so that the size of magnetite, which is a nano-scale material, is further reduced, and lanthanum is distributed in the magnetite bulk phase, and the specific surface area is relatively increased. Furthermore, the phenomenon of isomorphous replacement in magnetite is utilized to allow lanthanum to replace iron and enter the magnetite lattice. On the one hand, the strong magnetism of magnetite is preserved, which is beneficial to the recovery of materials; on the other hand, the loss of lanthanum during regeneration is low. At the same time, lanthanum ions enter the magnetite lattice and are preserved in the material during the regeneration cycle. Therefore, the isomorphous replacement magnetite material maintains a high phosphorus adsorption efficiency after multiple cycles, while avoiding the secondary pollution that may be caused by lanthanum ions entering the water body.

[0050] Based on the above preparation method, the present invention also provides a lanthanum isomorphous substitution magnetite material obtained by the preparation method, wherein lanthanum ions replace ferrous ions and enter the magnetite lattice.

[0051] Based on the above-mentioned lanthanum isomorphous substituted magnetite material, the present invention also provides an application of the lanthanum isomorphous substituted magnetite material in adsorbing phosphate ions in water purification.

[0052] Based on the above lanthanum isomorphous replacement magnetite material, the present invention also provides a phosphorus removal adsorbent for removing phosphate ions in water to be purified.

[0053] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings.

[0054] Example 1

[0055] (1) Lanthanum nitrate hexahydrate and ferrous sulfate heptahydrate were added to 60 ml of ethylene glycol solution containing 0.1 g of ascorbic acid, referred to as solution A. The total metal concentration in solution A was 9 mmol / L.

[0056] (2) Solution A was heated to 35°C, stirred vigorously for 30 min using a rotor, and then a 90 g / L sodium hydroxide solution was added and stirred for another 30 min. This was called Solution B.

[0057] (3) The solution B was sealed in a stainless steel reactor lined with polytetrafluoroethylene and maintained at 200° C. for 8 h to obtain a lanthanum isomorphous substituted magnetite material.

[0058] The structure of the obtained lanthanum isomorphous substituted magnetite material was determined by X-ray diffraction (XRD). Figure 2 The X-ray diffraction spectrum of the lanthanum isomorphous substituted magnetite material prepared in Example 1 corresponds to the standard diffraction peak of magnetite. The upper figure is the X-ray diffraction spectrum of the lanthanum isomorphous substituted magnetite material prepared in Example 1; the lower figure is the standard diffraction peak of magnetite (JCPDS: 19-0629). Figure 2 It can be seen that the lanthanum isomorphous substituted magnetite material prepared in Example 1 shows characteristic diffraction peaks belonging to magnetite.

[0059] The position of lanthanum in the obtained lanthanum isomorphous substituted magnetite material was determined using transmission electron microscopy (TEM). Figure 3 This is a transmission electron microscope image of the lanthanum isomorphous substituted magnetite material prepared in Example 1. Figure 3 The standard length of the marker is 100nm. Figure 3 Analysis found that there were no lanthanum hydroxide particles loaded on the surface of the magnetite material, which proved that lanthanum replaced iron and entered the magnetite lattice.

[0060] The phosphorus adsorption capacity of the lanthanum isomorphous substituted magnetite material was tested using a sequencing batch adsorption experiment. Figure 4 This is the phosphorus absorption curve of the lanthanum isomorphous substituted magnetite material prepared in Example 1 under different phosphate concentration conditions. Figure 4 As shown, the phosphate adsorption capacity of the lanthanum isomorphous substituted magnetite material is 115 mg·P / g·adsorbent. The lanthanum loss rate of the lanthanum isomorphous substituted magnetite material was analyzed by 8 adsorption-desorption cycles, and the results showed that the lanthanum loss rate was only 10%, and 83% of the adsorption capacity was maintained.

[0061] Example 2

[0062] (1) Lanthanum nitrate hexahydrate and ferrous sulfate heptahydrate were added to 50 ml of ethylene glycol solution containing 2 g / L ascorbic acid, referred to as solution A. The total metal concentration in solution A was 6 mmol / L.

[0063] (2) Solution A was heated to 25°C, stirred vigorously for 30 min using a rotor, and then 60 g / L sodium hydroxide was added and stirred for another 30 min. This was called Solution B.

[0064] (3) Solution B was sealed in a PTFE-lined stainless steel reactor and maintained at 200 °C for 6 h.

[0065] Transmission electron microscopy (TEM) analysis revealed that there were no small particles of lanthanum hydroxide on the surface of the material, and the shape changed from the original octahedron to an irregular polygon, proving that La(III) replaced iron into the magnetite lattice, rather than forming lanthanum hydroxide loaded on the magnetite surface. Batch adsorption experiments were used to test the phosphorus adsorption capacity of the lanthanum isomorphous replacement magnetite material, and its adsorption capacity for phosphate was 103 mg·P / g·adsorbent.

[0066] Example 3

[0067] (1) Lanthanum nitrate hexahydrate and ferrous sulfate heptahydrate were added to 80 ml of ethylene glycol solution containing 1.8 g / L ascorbic acid, referred to as solution A. The total metal concentration in solution A was 12 mmol / L.

[0068] (2) Solution A was heated to 35°C, stirred vigorously with a rotor for 30 min, and then 75 g / L sodium hydroxide was added and stirred for another 30 min. This was called Solution B.

[0069] (3) Solution B was sealed in a PTFE-lined stainless steel reactor and maintained at 300 °C for 10 h.

[0070] Batch adsorption experiments were used to test the phosphorus adsorption capacity of the lanthanum isomorphous substituted magnetite material, and the adsorption capacity of phosphate was 130 mg·P / g·adsorbent.

[0071] The reuse performance of the lanthanum isomorphous substituted magnetite material prepared by the method of Example 3 was compared and studied using 8 adsorption-desorption cycles. Figure 5 The figure is a comparison of the lanthanum loss rate of the lanthanum isomorphous substitution magnetite material and the lanthanum hydroxide-magnetite composite prepared by the method of Example 3 in 8 adsorption-desorption cycles. Figure 5 As shown, the lanthanum loss rate of the lanthanum isomorphous substituted magnetite material prepared by the method of Example 3 is less than 10%, while the lanthanum loss rate of the lanthanum hydroxide-magnetite composite is as high as 42%. Figure 6 The graph is a graph showing the change in phosphorus adsorption during each adsorption-desorption cycle of the lanthanum isomorphous substituted magnetite material prepared by the method of Example 3. Figure 6 As shown, the phosphorus adsorption capacity of the lanthanum isomorphous substituted magnetite material prepared by the method of Example 3 is still maintained above 75% after multiple cycles.

[0072] So far, the various embodiments of the present invention have been introduced.

[0073] In summary, the present invention provides a lanthanum-doped magnetite prepared by isomorphous replacement, so that the size of magnetite, which is a nano-scale material, is further reduced, and lanthanum is distributed in the bulk phase of the magnetite, and the specific surface area is relatively increased. In the preparation method, ferrous salts are selected instead of iron salts as the replaced material, and ascorbic acid is added to solution A to prevent divalent iron from being oxidized to trivalent iron, and a hydrothermal kettle is used to carry out a hydrothermal chemical reaction to increase the reaction temperature, thereby ensuring that lanthanum ions replace ferrous ions in the magnetite lattice. The lanthanum isomorphous replacement magnetite material of the present invention maintains the excellent recyclability of magnetite, and can give play to the selective adsorption of lanthanum to phosphate, while fixing lanthanum in the bulk phase to avoid its loss after adsorbing phosphate in the water body, and at the same time avoiding the problem of secondary pollution of lanthanum, and has good application prospects.

[0074] It should be noted that for certain implementations, if they are not the key content of the present invention and are well known to ordinary technicians in the relevant technical field, they are not described in detail in the drawings or the body of the specification. In this case, they can be understood by referring to the relevant prior art. The above part has described the embodiments of the present invention as detailed as possible in combination with the drawings. Based on the above description, those skilled in the art should have a clear understanding of the present invention.

[0075] In the description of the present invention, unless expressly indicated to the contrary, the numerical parameters in the specification and claims of the present invention may be approximate values ​​and can be changed according to the content of the present invention. Specifically, all the numbers recorded in the specification and claims indicating the content of the composition, reaction conditions, etc., should be understood to be modified by the term "about" in all cases, and the meaning of the expression is to include a change of ±10% in some embodiments, a change of ±5% in some embodiments, a change of ±1% in some embodiments, and a change of ±0.5% in some embodiments by a specific number. Furthermore, the word "comprising" does not exclude the existence of steps not listed in the claims.

[0076] The ordinal numbers used in the specification and claims, such as Arabic numerals, letters, etc., to modify the corresponding steps are intended only to make a step with a certain name clearly distinguishable from another step with the same name, and do not mean that the step has any ordinal number, nor do they represent the order of one step and another step.

[0077] Similarly, it should be understood that in order to simplify the present invention and help understand one or more of the various inventive aspects, in the above description of the exemplary embodiments of the present invention, the various features of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, the method of the invention should not be interpreted as reflecting the following intention: the claimed invention requires more features than the features explicitly stated in each claim. More specifically, as reflected in the claims, each inventive aspect is less than all the features of the previous single embodiment. Moreover, the embodiments can be mixed and matched with each other or with other embodiments based on design and reliability considerations, that is, the technical features in different embodiments can be freely combined to form more embodiments. Therefore, the claims following the specific embodiment are hereby explicitly incorporated into the specific embodiment, wherein each claim itself serves as a separate embodiment of the present invention.

[0078] The above specific embodiments provide a detailed description of the objectives, technical means and beneficial effects of the present invention. It should be understood that the purpose of the detailed description is to enable those skilled in the art to understand the present invention more clearly, and it is not used to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a lanthanum isomorphous substitution magnetite material, characterized in that: include: Adding lanthanum salt and ferrous salt to an ethylene glycol solution containing a reducing agent, referred to as solution A, wherein the lanthanum salt is lanthanum nitrate; the ferrous salt is ferrous sulfate, and the reducing agent is one or more of the following materials: ascorbic acid, hydrazine hydrate, formic acid; Adding an alkaline solution to solution A, referred to as solution B, wherein the alkaline solution is an alkaline solution containing hydroxide ions; The solution B is subjected to a hydrothermal chemical reaction to obtain a lanthanum isomorphous substitution magnetite material, wherein the solution B is added to a hydrothermal kettle and then subjected to a hydrothermal chemical reaction in an oven, the heating temperature of the oven being 200-300° C. and maintained for 6-10 hours.

2. The preparation method according to claim 1, characterized in that: The lanthanum nitrate is lanthanum nitrate hexahydrate; the ferrous sulfate is ferrous sulfate heptahydrate; and the reducing agent is ascorbic acid.

3. The preparation method according to claim 2, characterized in that: The molar ratio of the lanthanum nitrate hexahydrate to the ferrous sulfate heptahydrate is between 1:99 and 1:19; and / or In the ethylene glycol solution containing the reducing agent, the mass concentration of the ascorbic acid is 0.25-1.5 mg / mL; and / or In the solution A, the total molar concentration of lanthanum ions and ferrous ions is between 6 and 12 mmol / L.

4. The preparation method according to claim 1, characterized in that: In the step of adding an alkaline solution to solution A, the alkaline solution is a sodium hydroxide solution or a potassium hydroxide solution.

5. The preparation method according to claim 1, characterized in that: Before the step of adding the alkaline material to the solution A, the solution A is maintained at 25-35° C. and stirred by a rotor for 30-60 min; and / or After the step of adding the alkaline material to solution A, stirring solution B for 30 to 60 minutes; and / or In the step of adding an alkaline solution to solution A, the alkaline solution is a sodium hydroxide solution with a concentration of 50 to 120 g / L; and / or In the step of subjecting solution B to a hydrothermal chemical reaction, the hydrothermal chemical reaction is carried out in a hydrothermal kettle, which is a stainless steel reactor lined with polytetrafluoroethylene.

6. A lanthanum isomorphous substitution magnetite material, characterized in that: The method is as claimed in any one of claims 1 to 5, wherein lanthanum ions replace ferrous ions and enter the magnetite lattice.

7. Use of the lanthanum isomorphous substituted magnetite material as claimed in claim 6 for adsorbing phosphate ions in water purification.

8. A phosphorus removal adsorbent, characterized in that: include: The lanthanum isomorphous substituted magnetite material as claimed in claim 6.